STUDENTS' SPEAKING ABILITY THROUGH SMALL GROUP DISCUSSION - Atiiqah Mardhiyah; Aswadi Jaya; Yuspar Uzer (Esteem Journal of English Education Study Programme, 2023)
The purpose of this study was that students could communicate fluently using English in everyday life, using small group discussion strategies to make students more active in interacting with others. To collect the data for this research, the writer conduct in interview and questionnaire with the eight grade students at Junior High School Bina Jaya of Palembang. Each student will be given a paper like a questionnaire. The author will discuss the results of the research that has been done, namely using the small group discussion technique in learning speaking skills of students in the eighth grade. From the results of the questionnaire data processing, it can be seen from the statement item no.32 "Small group discussion techniques can improve students ''speaking skills". Most of the students chose 8 (50%) of the 16 respondents answered fully agree, while the rest chose 8 (50%) of the 16 respondents answered agree. Then the dominant result is balanced. The overall results of the study showed that small group discussions can effectively improve students' speaking skills, they actively conduct group discussions with their friends. Allow them to have an opinion and help each other, without mocking or laughing at each other.